ANALISA FAKTOR-FAKTOR RASIO KEUANGAN TERHADAP PERAMALAN TARGET TAKEOVER TAHUN 2005 - HOTMAN T. POHAN (Media Riset Akuntansi, Auditing & Informasi, 2008)
This research intend to continue last research about takeover and Q ratio that using discriminant analysis.ln this research discriminant analysis connot be applied because it does not fulfill the assumption,therefore the analysis in this research uses logit regression analysis. By using logit regression analysis,writer get model that has been tested its validity and hypothesis of this research can be proved.The hypothesis is that certain ratio can predict the possibility of taking over company target.By cutting 5O% off ,a company can be concluded and classified wether it deserves or not to be taken over. Ebitda to sales on behalf DER and CFO to sales ratio has positive sign in logit regression probability model,it means that EBITDA to sales enhance the probability of taking over On the other hand, ROE and PBV ratio have negative sign in this model,it means that these ratio lessen the probability of taking over.Keywords: takeover, q ratio, logit regression probability model